Improved Overall Survival, Relapse-Free-Survival, and Less Graft-vs.-Host-Disease in Patients With High Immune Reconstitution of TCR Gamma Delta Cells 2 Months After Allogeneic Stem Cell Transplantation - Minculescu, Lia; Marquart, Hanne Vibeke; Ryder, Lars Peter; Andersen, Niels Smedegaard; Schjoedt, Ida; Friis, Lone Smidstrup; Kornblit, Brian Thomas; Petersen, Søren Lykke; Haastrup, Eva; Fischer-Nielsen, Anne; Reekie, Joanne; Sengelov, Henrik (Frontiers in Immunology, 2019)
T-cell receptor (TCR) γδ cells are perceived as innate-like effector cells with the possibility of mediating graft-versus-tumor (GVT) without causing graft-versus-host disease (GVHD) in the setting of hematopoietic allogeneic stem cell transplantation (HSCT). We conducted a prospective study to assess the clinical impact of TCR γδ cell immune reconstitution on overall survival, relapse-free-survival, relapse and GVHD. The impact of CD3, CD4, CD8 T cells together with NK cells including subtypes were analyzed in parallel. A total of 108 patients with hematological malignancies transplanted with HLA-matched, T cell replete stem cell grafts were included for analyses of absolute concentrations of CD3, CD4 and CD8 positive T cells and NK cells together with a multi-color flow cytometry panel with staining for TCRαβ, TCRγδ, Vδ1, Vδ2, CD3, CD4, CD8, HLA-DR, CD196, CD45RO, CD45RA, CD16, CD56, CD337 and CD314 at 28, 56, 91, 180 and 365 days after transplantation. Immune reconstitution data including subsets and differentiation markers of T and NK cells during the first year after transplantation was provided. Patients with TCR γδ cell concentrations above the median value of 21 (0-416) x106 cells/L 56 days after transplantation had significantly improved overall survival (p=0.001) and relapse-free survival (p=0.007) compared to patients with concentrations below this value. When day 56 cell subset concentrations were included as continuous variables, TCR γδ cells were the only T cell subsets with a significant impact on OS and RFS; the impact of TCR γδ cells remained statistically significant in multivariate analyses adjusted for pre-transplant risk factors. The risk of death from relapse was significantly decreased in patients with high concentrations of TCR γδ cells 56 days after transplantation (p=0.003). Also, the risk of acute GVHD was significantly lower in patients with day 28 TCR γδ cell concentrations above the median of 18x106 cells/L compared to patients with low concentrations (p=0.01). These results suggest a protective role of TCR γδ cells in relapse and GVHD and encourage further research in developing adaptive TCR γδ cell therapy for improving outcomes after HSCT.